2013
DOI: 10.1016/j.neuropharm.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of metabotropic glutamate receptors in persistent forms of hippocampal plasticity and learning

Abstract: Storage and processing of information at the synaptic level is enabled by the ability of synapses to persistently alter their efficacy. This phenomenon, known as synaptic plasticity, is believed to underlie multiple forms of long-term memory in the mammalian brain. It has become apparent that the metabotropic glutamate (mGlu) receptor is critically required for both persistent forms of memory and persistent synaptic plasticity. Persistent forms of synaptic plasticity comprise long-term potentiation (LTP) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 292 publications
3
74
0
1
Order By: Relevance
“…For example, mGluR5 has important roles in two opposing forms of synaptic plasticity in the hippocampus. These include the long-term potentiation (LTP) and long-term depression (LTD) of synaptic strength, each of which is induced by highly specific patterns of activity of glutamatergic afferents 139 . When mGluR5 is activated by glutamate that is released from the terminals of afferents that fire with low frequency, it induces LTD (or a weakening of synaptic connections).…”
Section: Figurementioning
confidence: 99%
“…For example, mGluR5 has important roles in two opposing forms of synaptic plasticity in the hippocampus. These include the long-term potentiation (LTP) and long-term depression (LTD) of synaptic strength, each of which is induced by highly specific patterns of activity of glutamatergic afferents 139 . When mGluR5 is activated by glutamate that is released from the terminals of afferents that fire with low frequency, it induces LTD (or a weakening of synaptic connections).…”
Section: Figurementioning
confidence: 99%
“…Based on the results from our study, repeated dosing with CDPPB shows significant enhancement of performance in the T-maze, suggesting that subtle changes in receptor density may not affect learning. Spatial learning in rodents is strongly correlated to hippocampal synaptic plasticity and mGlu5 receptors play a critical role in multiple forms of synaptic plasticity both in vitro and in vivo (reviewed by Mukherjee & Manahan-Vaughan, 2012). Interestingly, mGlu5 receptor PAMs are able to enhance both LTP and LTD in the hippocampus (Ayala et al, 2009).…”
Section: Test Daymentioning
confidence: 99%
“…Group III mGlu receptors are thought to be involved in a number of short-and long-term forms of synaptic plasticity within the hippocampus and dentate gyrus, and are most frequently associated with long-term depression (LTD) [199,200]. Thus, a key study by Pelkey et al [149] in 2005 revealed that HFS, or application of high concentrations of L-AP4, induces a form of LTD at mossy fiber-CA3 interneuron synapses that is mGlu7-dependent.…”
Section: Hippocampal Plasticitymentioning
confidence: 99%